Memory and the Language of Contention - Elzen, Sophie van den,; Rigney, Ann, (Literature and Cultural Studies E-Books Online, Collection 2025., 2025)
How does language shape the memory of activism? And how do memories, of hope or of repression, inflect the language used by social movements in the present day? This edited volume, featuring international scholars across literary and cultural studies, anthropology, legal studies, and linguistics, shows how memories of activism live in the medium of language. It contends that working with, and working on, the historical resonance of words and linguistic commonplaces is a central feature of political contention.